Subtitling Taboo Language: Using the Cues of Register and Genre to Affect Audience Experience? - Baines, Roger (Meta, 2015)
Using French-English/English-French examples, this article puts forward the hypothesis that, in the film genre of social realism (depicting low socio-economic groups), subtitlers use linguistic and visual cues which are embedded in genre to trigger audience reactions to representations of taboo language. Examples of the subtitling of taboo language are drawn from three films and the hypothesis above will be explored along three main interrelated axes: i) the value of treating subtitles as an entire system; ii) the relationship between the specific film genre of social realism (depicting low socio-economic groups) and audience perceptions of taboo language use; and iii) discourse representations through register and its effect on characterisation. Nuances are brought to evidence from existing research which argues that the choices relating to taboo language made in the oral to written mode shift are subject to politeness restrictions in terms of register, and that these choices have a homogenising/levelling effect on characterisation (Lambert 1990; Taylor 2006a; Mailhac 2000 for example).